The Solomonic Corpus of ‘Wisdom’ and its Influence By Katharine J. Dell - Cheung, Simon Chi-chung (The journal of theological studies, 2024)
This book comprises 13 articles, mostly written over the last two decades, but three (chapters 4, 9, 13) newly written for this project. A collection of es